EFFECTIVE USE OF MNEMONICS IN TEACHING THE RUSSIAN LANGUAGE (American Journal of Interdisciplinary Research and Development, 2024)
The article "Effective use of mnemotics in teaching Russian" discusses the use of mnemotics in teaching Russian. Mnemonics is an effective tool to help you remember data using associations, images and memorable images. The article provides methodological recommendations such as the creation of associations, the use of mental maps, the development of coconuts and songs, as well as the use of gaming techniques. These methods encourage students to remember the rules of vocabulary, grammar, and help students develop their language skills. The use of mnemonics in the learning process makes learning Russian more interesting, effective and interactive, helps to activate cognitive processes and improve learning outcomes.